Impact of red mud on soil properties and revegetation species growth in bauxite mining land reclamation - Sulakhudin; Herawatiningsih, Ratna; Krisnohadi, Ari; Abdillah, Andi Massoeang; Santi; Mudim (Brawijaya University, 2024)
Bauxite mining, a key aluminum production process, can cause environmental degradation, soil erosion, and biodiversity loss. Reclamation measures like reforestation and water management can restore balance. Red mud, a by-product of alumina production, can enhance soil fertility and plant growth in post-bauxite mining reclamation areas. Its alkalinity and mineral composition reduce reliance on synthetic fertilizers, promoting sustainable soil management and addressing environmental challenges. This study aimed to examine the impact of red mud on soil characteristics and the growth of plants in areas during bauxite mining land reclamation. This study was conducted in the post-reclamation area of bauxite mining in West Kalimantan. The experiment involved two treatments: red mud application and a species of revegetation plant. Plant species consist of the plants Embeng, Forest Guana, Johar, and Rambutan. The study used a randomized block design with 24 experimental units. The parameters measured in the study included pH, organic carbon, nitrogen, phosphorus, exchangeable cations, cation exchange capacity, and base saturation, while growth parameters included a high percentage of plant growth and percentages of increased stem diameter. The findings showed that adding red mud to the planting hole increased soil pH and base saturation, improved nutrient availability, and enhanced plant growth in the areas post-mining bauxite at PT Antam, UBPB West Kalimantan. The Embeng Plant is highly regarded as a suitable plant species for re-vegetating areas after bauxite mining.